Completely predatory development is described in a braconid wasp - A. P. Ranjith; Donald L. J. Quicke; K. Manjusha; Buntika A. Butcher; M. Nasser (Scientific Reports, 2022)
Abstract Hymenopteran parasitoids are well known for their ubiquitous diversity, important ecological roles and biocontrol potential. We report the first detailed documentation of mite predation by a parasitoid wasp, Bracon predatorius Ranjith & Quicke sp. nov., (Insecta: Hymenoptera), first case of obligate predatory behaviour in the family Braconidae and first case of mite feeding within the superfamily Ichneumonoidea. Larvae of a new wasp species are shown to develop entirely as predators of eriophyid mites that induce leaf galls in a commercially important plant. They display highly modified head capsule morphology that we interpret as being associated with this atypical life style. We propose that the new feeding strategy evolved separately from recently described entomophytophagy in another species of the same genus. The divergent larval morphological adaptations of both species indicate a high degree of evolutionary developmental plasticity in the developmental stage.